POUR after spinal anesthesia in lower limb orthopaedic surgeries-a prospective study - Sen, Anuradha; Singh, Omeshwar (International Journal of Research in Medical Sciences, 2018)
Background: Postoperative urinary retention (POUR) is a common problem with overall rates looking at the entire surgical population quoted between 4% and 6%. POUR has been defined as the inability to void in the presence of a full bladder. Methods: This was a prospective, single-centre, observational study conducted between June 2015 to December 2016 at a tertiary care centre of Northern India. The study group enrolled 186 patients undergoing various lower limb surgeries under spinal anesthesia. Results: In the present study, out of 186 patients, 101 patients were male and 85 patients were female. Most of the patients were in the 41-60 years age group (78) followed by 72 patients were in the >61 years age group. 21 patients (11.29%) suffered with post operative urine retention (POUR) in whom catheterization was required, the incidence of POUR in joint replacement surgeries was 20.96% (13/62). In the present study incidence of POUR was more in males (12 patients) as compared to females (9 patients). POUR was more common in the elderly age group. Conclusions: By carefully identifying patients at risk, adopting appropriate anesthetic techniques and perioperative care principles and accurately monitoring bladder volume by ultrasound, POUR may be prevented and the associated morbidity minimized. Hence it becomes imperative to evaluate the true incidence and consequences of POUR in large prospective clinical studies. Spontaneous micturition should remain a criterion for discharge after spinal anaesthesia.